DOI: 10.53846/goediss-8259
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Nitrogen Nutrition and Ectomycorrhizal Interaction on Populus x canescens Xylem Sap Composition and Defense

Abstract: liquid chromatography GO:0010023 2.72 7.46E-05 proanthocyanidin biosynthetic process GO:0006559 2.37 4.36E-03 L-phenylalanine catabolic process GO:1902222 2.37 4.36E-03 erythrose 4-phosphate/phosphoenolpyruvate family amino acid catabolic process GO:0009074 2.35 4.40E-04 aromatic amino acid family catabolic process GO:0019632 2.33 2.26E-02 shikimate metabolic process GO:0046271 2.15 3.30E-06 phenylpropanoid catabolic process GO:0046274 2.15 3.30E-06 lignin catabolic process GO:0009819 2.1 2.69E-03 drought reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 245 publications
0
1
0
Order By: Relevance
“…In AMF and rhizobia symbiosis, specific small peptides transported via the xylem are required to establish symbiosis (Le . A multi-omics study found metabolites such as flavonol rhamnetin, which has antimicrobial properties (Papp, 2005), and proteins such as SAR long-distance signal DEFECTIVE IN INDUCED RESISTANCE1 enriched in the xylem sap of ectomycorrhizal poplar compared to non-inoculated poplar but could not identify the mobile signal required for systemic effects (Kasper, 2020).…”
Section: The Systemic Signal In Systemic Ectomycorrhizal Defense Is U...mentioning
confidence: 99%
“…In AMF and rhizobia symbiosis, specific small peptides transported via the xylem are required to establish symbiosis (Le . A multi-omics study found metabolites such as flavonol rhamnetin, which has antimicrobial properties (Papp, 2005), and proteins such as SAR long-distance signal DEFECTIVE IN INDUCED RESISTANCE1 enriched in the xylem sap of ectomycorrhizal poplar compared to non-inoculated poplar but could not identify the mobile signal required for systemic effects (Kasper, 2020).…”
Section: The Systemic Signal In Systemic Ectomycorrhizal Defense Is U...mentioning
confidence: 99%